Killin Smallz [videorecording (DVD)] - Martin, Ray; Guiry, Thomas, 1981-; Darrow, Tony; D'onofrio, Joseph; Borghese, Paul (Dreamscape Media, 2023)
A mob family that is not earning as they did in the past comes up with a crazy idea after watching the movie Stealing a Survivor to kidnap someone famous for ransom.